Derivative Spectrophotometric Methods for the Determination of Tilorone - An Antiretroviral Drug - Annapurna, Mukthinuthalapati Mathrusri (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: New spectrophotometric methods have been developed for the determination of Tilorone in pharmaceutical formulations. Spectrophotometric techniques have been proposed for the determination of Tilorone in sodium acetate buffer (pH 4), borate buffer (pH 9), and phosphate buffers (pH 2.0 and pH 5.0). Materials and Methods: Shimadzu UV-1800 model ultraviolet-visible spectrophotometer double beam was used for the present study. Three different spectrophotometric techniques were developed using sodium acetate buffer (pH 4), borate buffer (pH 9), and phosphate buffers (pH 2.0 and pH 5.0). Results and Discussion: Tilorone has shown absorption maxima at 270 nm, and linearity 0.4–14 μg/mL in all the three methods in all the four buffer solutions and all the methods were validated as the per ICH guidelines. Conclusions: These methods are simple, economical and can be successfully applied for the estimation of tilorone in pharmaceutical dosage forms.